A Rising Star in Pancreatic Diseases: Pancreatic Stellate Cells - Xue, Ran; Jia, Kai; Wang, Jianxin; Yang, Lixin; Wang, Yanbin; Gao, Lingyun; Hao, Jianyu (Frontiers in Physiology, 2018)
Pancreatic stellate cell (PSC) is a type of pluripotent cell located between pancreatic lobules and the surrounding area of acinars. When activated, PSC can be transformed into myofibroblast-like cell. A number of evidences suggest that activated PSC is the main source of the accumulation of extracellular matrix (ECM) protein under the pathological conditions, which lead to pancreatic fibrosis in chronic pancreatitis and pancreatic cancer. Recent studies have found that PSC also plays an important role in the endocrine cell function, islet fibrosis and diabetes. In order to provide new strategies for the treatment of pancreatic diseases, this paper systematically summarizes the recent researches about the biological behaviors of PSC, including its stem/progenitor cell characteristics, secreted exosomes,cellular senescence, epithelial interstitial transformation (EMT), energy metabolism and direct mechanical reprogramming.